Measuring physical activity levels in hospitalized patients: a comparison between behavioural mapping and data from an accelerometer. (July 2019) - Valkenet, Karin; Bor, Petra; van Delft, Lotte; Veenhof, Cindy
Objective: To investigate the level of agreement of the behavioural mapping method with an accelerometer to measure physical activity of hospitalized patients. Design: A prospective single-centre observational study. Setting: A university medical centre in the Netherlands. Subjects: Patients admitted to the hospital. Main measures: Physical activity of participants was measured for one day from 9 AM to 4 PM with the behavioural mapping method and an accelerometer simultaneously. The level of agreement between the percentages spent lying, sitting and moving from both measures was evaluated using the Bland–Altman method and by calculating Intraclass Correlation Coefficients. Results: In total, 30 patients were included. Mean (±SD) age was 63.0 (16.8) years and the majority of patients were men ( n  = 18). The mean percentage of time (SD) spent lying was 47.2 (23.3) and 49.7 (29.8); sitting 42.6 (20.5) and 40.0 (26.2); and active 10.2 (6.1) and 10.3 (8.3) according to the accelerometer and observations, respectively. The Intraclass Correlation Coefficient and mean difference (SD) between the two measures were 0.852 and –2.56 (19.33) for lying; 0.836 and 2.60 (17.72) for sitting; and 0.782 and −0.065 (6.23) for moving. The mean difference between the two measures is small (⩽2.6%) for all three physical activity levels. On patient level, the variation between both measures is large with differences above and below the mean of ⩾20% being common. Conclusion: The overall level of agreement between the behavioural mapping method and an accelerometer to identify the physical activity levels 'lying', 'sitting' and 'moving' of hospitalized patients is reasonable.